KLASIFIKASI GENUS TANAMAN ANGGREK MENGGUNAKAN CONVOLUTIONAL NEURAL NETWORK (CNN) DENGAN MENGGUNAKAN ARSITEKTUR VGG 16 - Zulkipli; Akbar, Lalu A. Syamsul Irfan; Kanata, Bulkis (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
Indonesia is one of the countries that has very diverse orchid genetic resources. Orchid species are found in several islands in Indonesia such as Java, Sumatra, Kalimantan, Sulawesi, Nusa Tenggara, Bali, Maluku and Papua and have types of orchids with varying flower characters. Orchids are one of the most popular ornamental plants and have a beautiful charm. The beauty and value of orchids are in their flowers. However, some orchids have the same color and appearance even though they belong to different species. In fact, many people think that one orchid species with other species that have similar shapes are the same species. Therefore, a system is needed that can make it easier to recognize orchid species. The method used is the Convolutional Neural Network with VGG 16 Architecture to classify orchid flower types, where the dataset used is divided into 3 scenarios, namely scenario 1 using orchid petal images, scenario 2 using orchid leaf tree images, and scenario 3 using combined images of orchid flower petals and leaves. From the three scenarios, the results of the model with high accuracy in scenario 3 were 99.47%. This shows that the model built is able to predict well.